Volunteer Movement in the Context of Formation and Development of Civil Society in Ukraine - Grabovska, Iryna (Київський національний університет імені Тараса Шевченка, 2017)
The author of the article analyzes the formation of a developed civil society in Ukraine through the developmentof modern mass volunteer movement. The mass volunteer movement in the country especially assists the Ukrainian army, which isfighting with aggression from Putin's Russia in Eastern Ukraine. The author traces the origins and growth of civil activity of voluntarymutual aid society of events leading Ukrainian Revolution of Dignity. The work exams mass movement of volunteers during theMaidan (Pro European Revolution) of 2013-2014th. During the years of Ukrainian independence intellectuals both in Ukraine and inthe Diaspora were active quest for consolidating society, society and government factors. At the beginning of Ukrainianindependence, analysts and scientists great hopes pinned on finding and functioning of the national idea. It had to consolidatearound him and lead the nation forward. This approach had its theoretical basis. However, post-colonial reality in Ukraine has placedmore emphasis. The priority factor in national consolidating towards its transformation into a political nation was civil society. Theresearcher develops the idea that at the present stage of historical development of Ukrainian society the main factor consolidatingthe nation it serves volunteering. It is the clearest example of the functioning of civil society in Ukraine. The author also analyzes thetheoretical basis of consolidating consideration factors put forward as basic of Ukrainian social-humanitarian studies in past years ofindependence. In particular, it is a national idea. The author emphasizes that the events in the transitional post-colonial society hasits own specifics. This specificity determines the priorities for transformation. The researcher concludes on extraordinary importanceof volunteering and volunteerism for the preservation of Ukrainian independence, a full-fledged political nation on the territory ofmodern Ukraine and incorporating the country into European community. The author points to the need to consider gendercharacteristics of volunteering in Ukraine. The gender factor is taken into account, in particular, to overcome social injustice and apolicy of non-discrimination in Ukraine.Key words: volunteering, volunteerism, civil society, political nation, consolidating factor, Ukrainians

Ірина Грабовська Авторка статті аналізує становлення розвинутого громадянського суспільства в сучасній Україні через розвиток масового волонтерського руху. Масовий волонтерський рух в країні насамперед спрямований на допомогу українській армії, яка бореться з агресією з боку путінської Росії на Сході України. Автор прослідковує витоки громадянської активності та наростання добровільної взаємодопомоги у суспільстві від подій, що передували українській Революції Гідності. Робота розглядає волонтерство широких народних мас українства під час Єврореволюції 2013 – 2014 рр. Протягом усіх років української незалежності інтелектуали як в Україні, так і в діаспорі вели активні пошуки консолідуючих для суспільства, соціуму та держави факторів. На початку української незалежності аналітики та науковці особливі надії покладали на віднайдення та функціонування національної ідеї. Вона мала довкола себесконсолідувати націю і повести вперед. І такий підхід мав своє теоретичне підґрунтя. Проте, постколоніальна реальність в Україні розставила інші акценти. Пріоритетним фактором консолідації нації на шляху перетворення її в політичну націю стало громадянське суспільство. Дослідниця розвиває ідею про те, що на сучасному етапі історичного розвитку українського суспільства головним консолідуючим націю чинником виступає саме волонтерський рух. Він є найяскравішим прикладом функціонування громадянського суспільства в Україні. Авторка аналізує також теоретичні засади розгляду консолідуючих факторів, які висувались як базові українською соціогуманітаристикою протягом попередніх років незалежності. Зокрема, мова йде про національну ідею. Авторка наголошує, що перебіг подій в перехідному постколоніальному соціумі має свою специфіку. Ця специфіка визначає пріоритетні напрямки трансформацій. Дослідниця робить висновок щодо непересічної значимості волонтерства та волонтерського руху для збереження української незалежності, формування повноцінної політичної нації на теренах сучасної України та вписування країни у спільний європейський простір. Авторка вказує на необхідність врахування гендерних характеристик волонтерства в Україні. Гендерний чинник варто враховувати, зокрема, для подолання соціальної несправедливості та проведення політики недискримінації в Україні. Ключові слова: волонтер, волонтерство, громадянське суспільство, політична нація, консолідуючий фактор, українці.
Волонтерський рух у контексті становлення та розвитку громадянського суспільства в Україні